vNMF: Distributed fault detection using clustering approach for network function virtualization - Miyazawa, Masanori; Hayashi, Michiaki; Stadler, Rolf (2015 IFIP IEEE International Symposium on Integrated Network Management (IM), 2015)
Network function virtualization introduces additional complexity for network management through the use of virtualization environments. The amount of managed data and the operational complexity increases, which makes service assurance and failure recovery harder to realize. In response to this challenge, the paper proposes a distributed management function, called virtualized network management function (vNMF), to detect failures related to virtualized services. vNMF detects the failures by monitoring physical-layer statistics that are processed with a self-organizing map algorithm. Experimental results show that memory leaks and network congestion failures can be successfully detected and that and the accuracy of failure detection can be significantly improved compared to common k-means clustering.